2011
DOI: 10.1038/ejhg.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lynch syndrome modifier genes in 748 MMR mutation carriers

Abstract: Several studies have reported that, in Lynch syndrome resulting from mutations of the mismatch repair (MMR) genes, a CA repeat r17 within the IGF1 promoter, SNPs within the xenobiotic metabolizing enzyme gene CYP1A1 and SNPs on 8q23.3 and 11q23.1 modify colorectal cancer (CRC) risk in MMR mutation carriers. We analysed the impact of these polymorphisms on CRC risk in 748 French MMR mutation carriers derived from 359 families. We also analysed the effect of the Novel 1 SNP (18q21), which has recently been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…Previous works have found the modifying effects of common SNPs in carriers of mismatch repair gene mutations; 36 however these results were not replicated in other studies. 37, 38 Using family history as a surrogate, we found that the genetic risk score of common loci remains to be significantly associated with increased risk of CRC in both men and women with a positive family history of CRC (results not shown), suggesting common genetic loci improve risk prediction in this group. Second, although our independent validation study includes approximately 1,800 subjects, we validated the models for men (~1,100) and women (~700) separately; therefore, the sample size is somewhat limited.…”
Section: Discussionmentioning
confidence: 91%
“…Previous works have found the modifying effects of common SNPs in carriers of mismatch repair gene mutations; 36 however these results were not replicated in other studies. 37, 38 Using family history as a surrogate, we found that the genetic risk score of common loci remains to be significantly associated with increased risk of CRC in both men and women with a positive family history of CRC (results not shown), suggesting common genetic loci improve risk prediction in this group. Second, although our independent validation study includes approximately 1,800 subjects, we validated the models for men (~1,100) and women (~700) separately; therefore, the sample size is somewhat limited.…”
Section: Discussionmentioning
confidence: 91%
“…12 These results were partly confirmed in a cohort of Australian and Polish MMR mutation carriers, but were not replicated in a French cohort. 13,14 We selected the hTERT variant rs2075786 by somehow combining candidate gene and GWAS-based approaches. First, hTERT has an important role at very early stages of carcinogenesis, its expression has been linked to increased susceptibility to tumorigenesis, and rs2075786 has been associated with cancer risk.…”
Section: Rs2075786 and Telomere Lengthmentioning
confidence: 99%
“…11 In contrast, two genetic variants previously identified in CRC genome-wide association studies (GWAS), rs16892766 and rs3802842, might modify cancer risk in LS families. [12][13][14] Telomeres are located at the end of chromosomes and protect the chromosome ends from nucleolitic degradation, end-to-end fusions and irregular recombination, being thus critical for genome stability and integrity. Telomeres progressively shorten with each cell replication cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, the association was stronger for CRC diagnosed under age 60 years suggesting potential age modifying effects in MMR gene mutation carriers. This SNP has also been reported as a CRC risk modifier for MMR gene mutation carriers in three other studies(1315); but not in one study(16). Talseth-Palmer et al(14) did not observe a significant effect of rs16892766 alone on CRC risk but observed a trend of an increased risk of CRC for the pair-wise combination of SNPs rs3802842 and rs16892766 in MLH1 mutation carriers.…”
Section: Discussionmentioning
confidence: 87%
“…If these SNPs also predicted CRC risk in MMR gene mutation carriers, there would be a potential to use them to more accurately predict individual risk estimates for Lynch syndrome. Three studies observed two variants, 8q23.3 (rs16892766) and 11q23.1 (rs3802842), to be associated with increased risk of CRC in Lynch syndrome especially for females only(13, 14) or MLH1 mutation carriers only(14, 15); however, another study(16) observe no associations. In this study of MMR gene mutation carriers, we have investigated associations of CRC with SNPs at 11 loci: 8q23.3 (rs16892766), 8q24.21 (rs6983267), 9p24 (rs719725), 10p14 (rs10795668), 11q23.1 (rs3802842), 14q22.2 (rs4444235), 15q13.3 (rs4779584), 16q22.1 (rs9929218), 18q21.1 (rs4939827), 19q13.1 (rs10411210) and 20p12.3 (rs961253).…”
Section: Introductionmentioning
confidence: 99%